Learning in the internet era: exploring the benefits and challenges of a new communication paradigm - Coutinho, Clara Pereira (2008)
In the global web of information we call Internet, communication changed radically. Today we communicate at such a fast pace that the distances fade at an astonishing rate. In the Internet we communicate in a direct, real time fashion with the whole world. Never, in the history of mankind, ideas, information and products circulated so quickly and easily. In this article we will address the role of technologies, from teacher’s auxiliary means to powerful learning tools at the service of the student in the process of building knowledge. In a following stage, we will focus our attention on the communication on the global web of information we call Internet and on the challenges schools face today. We will also address the change in the Internet communications paradigm from web 1.0 to web 2.0, in which the user goes from consumer to producer of information. We will finish by presenting some web 2.0 tools and the great potential they offer to educational communication.